YouTube Channel Development on Education: Virtual Learning Solutions during the Covid-19 Pandemic - Edi Irawan, Ahmadi, Agus Prianggono, A.D. Saputro, M.S. Rachmandhani (International Journal of Advanced Science and Technology, 2020)
Covid-19 pandemic makes all activities that involve many people must be limited. Likewise, with lecture activities, it must be diverted online. The availability of supporting facilities and infrastructure is the main problem. This study aims to provide a solution by developing a YouTube Channel that contains learning material in applied statistics courses. Development is carried out using the ADDIE model which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Video creation and editing using Camtasia. After the learning media is developed, it is uploaded to the YouTube Channel and integrated into the Google Classroom. Based on the results of evaluations conducted by student users, it is known that learning media through the YouTube Channel that was developed is very useful, easy to use, and has a relatively very good quality. Clear evidence of media utilization can be seen from the results of the YouTube Channel analysis which shows a significant development of the viewer. Keywords: Covid-19, education, YouTube Channel, virtual learning.